Effects of Antiseizure Medications on Second-Trimester Prenatal Screening Test Parameters: A Retrospective Cohort Study - Golgelioglu, Melisa; Akcabay, Cigdem; Albayrak, Gunes Seda; Telo, Selda (Mdpi, 2025)
Background and Objectives: The use of antiseizure medications (ASMs) during pregnancy is critical to seizure control in women with epilepsy but raises concerns regarding the use of these drugs and their possible effect on the maternal serum biochemical markers used for second-trimester prenatal screening. The aim of this study was to assess the effect of ASMs on the levels of maternal serum alpha-fetoprotein (AFP), unconjugated estriol (uE3), and human chorionic gonadotropin (hCG) assessed in the serum biomarker analyses part of second-trimester prenatal screening. Materials and Methods: This retrospective cohort study included 43 pregnant women in the ASM-exposed group (levetiracetam, lamotrigine, carbamazepine, or combined therapy) and 43 matched controls without medication use. Groups were matched based on maternal age, gravidity, parity, abortion history, gestational age at testing, body mass index, and smoking status with propensity score matching. Serum AFP, uE3, and hCG levels measured at 15-20 weeks of gestation were compared between groups. The incidence of fetal congenital anomalies or aneuploidies was also compared between groups. Results: Pregnant women in the ASM-exposed group had significantly higher maternal serum AFP (1.34 +/- 0.42 vs. 1.01 +/- 0.31 MoM; p < 0.001) and uE3 (1.28 +/- 0.39 vs. 1.05 +/- 0.34 MoM; p = 0.004) than the controls. However, hCG did not differ significantly between the groups (1.07 +/- 0.46 vs. 1.01 +/- 0.42 MoM; p = 0.523). Regarding the ASM subgroups (levetiracetam, lamotrigine, and carbamazepine), there were no significant differences in the serum biomarkers (p > 0.05). There was no significant difference between the ASM-exposed and control groups in terms of the incidence of congenital anomalies or aneuploidies (2.3% in the ASM-exposed group vs. 2.3% in the control group; p = 1.000). Conclusions: The use of ASMs during pregnancy significantly alters second-trimester maternal serum biochemical markers, including our primary concerns, AFP and uE3, which could cause inaccurate interpretations of second-trimester prenatal screening. Clinicians should carefully consider maternal medication exposure when interpreting these biochemical markers in pregnant women with epilepsy to prevent the misclassification of fetal risks and avoid unnecessary invasive procedures.
Keywords: alpha-fetoprotein; fetal anomalies; human chorionic gonadotropin; teratogenicity; unconjugated estriol